Test of Stevia Leaf Ethanol Extract (Stevia Rebaudiana) Administered Orally to Female Wistar Rats (Rattus Norvegicus) on a High-Fat Diet to Prevent Dyslipidemia - Randy Suryadinata, Emmanuel; Hendriani Djuang, Michelle; Novriani, Erida; Merry Cisca, Anita (Jurnal EduHealth, 2023)
This study aims to analyze and test the effect of Stevia Rebaudiana ethanol extract in preventing dyslipidemia in female Wistar rats (Rattus Norvegicus) fed a high-fat diet. The results showed that giving Stevia Rebaudiana ethanol extract at 40 mg / 200 gr BW of female Wistar rats given a high-fat diet orally prevented a decrease in HDL cholesterol levels. However, it will increase total cholesterol, LDL cholesterol, and triglycerides. This study demonstrated that the ethanol extract of Stevia Rebaudiana has beneficial properties in controlling hyperlipidemia, which is presumably due to the antioxidant and glycoside effects of the ethanol extract of Stevia Rebaudiana, which overall contributes to the development profile lipid rats were given a high-cholesterol diet.